Pirólise rápida catalítica de sabugo de milho: seletividade dos catalisadores HZSM-5 e Hβ para a produção de hidrocarbonetos aromáticos - Silva, Amanda Carla Ribeiro da (2020)
The gradual depletion of fossil fuels and the growing concern about global warming motivated the search for renewable energy sources and alternative technologies for their generation. Thermochemical conversion processes applied to biomass, such as pyrolysis, are a promising and attractive strategy for the use of agro-industrial wastes and the generation of higher value-added products. Thus, this work aimed to study the fast pyrolysis of corn cob, an high and little-used waste. For this purpose, the physicochemical characterization analyses were performed to evaluate the potential application of this biomass in the production of biooil. The volatile matter, ash and moisture contents, as well as the contents of cellulose and hemicelluloses, were similar to those of other biomasses already used in fast pyrolysis, and pointed out the corncob as a possible candidate for this process. The decomposition kinetics of this biomass was investigated with the thermogravimetric experimental data obtained at the heating rates of 5, 10, 15, 20 and 25 °C/min. The kinetic parameters were estimated by the global reaction models, which presented mean apparent activation energy values ranging from 148.80 to 166.23 kJ/mol, and by the independent parallel reactions model (IPR), which indicated the occurrence of three reactions with distinct kinetics corresponding to the degradation of its main components. In this case, the estimated activation energy values for each component were: cellulose (156.78-160.80 kJ/mol), hemicelluloses (98.49-101.74 kJ/mol) and lignin (50.25-57.29 kJ/mol). Analytical pyrolysis tests were carried out with the pure biomass at 450, 550 and 650°C and the products were predominantly oxygenated compounds, including acids, ketones, phenols, alcohols, and furans, and revealed the little influence of the temperature on their thermal conversion. The 3k factorial design was employed along with the response surface methodology (RSM) to investigate the effect of the reaction temperature (450, 550, and 650°C) and catalyst mass concentration (1, 3, and 5 mg of catalyst/mg of biomass) on the response variables, the hydrocarbons content and oxygenated content, in the corn cob analytical pyrolysis. Two acid zeolites were used, HZSM-5 and Hβ. For both catalysts, the highest levels of the reaction temperature and catalyst mass concentration increased hydrocarbons selectivity while being effective in the vapor deoxygenation process, resulting in higher hydrocarbons content and lower oxygenated content. The operation of the fast pyrolysis experimental unit composed of a bubbling fluidized bed reactor provided the yields of bio-oil (16.96%), char (22.43%) and noncondensable gases (60.61%). The corncob bio-oil was characterized as a complex mixture of organic compounds, with a high content of phenolic compounds that are used in the production of resins, adhesives, polymers and as precursors of the pharmaceutical industry.